2019 IEEE Milan PowerTech 2019
DOI: 10.1109/ptc.2019.8810483
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Circuit Programming for Estimating the State of a Power System

Abstract: An Equivalent Circuit Programming (ECP) approach that expresses the optimality conditions of an optimization problem in terms of an equivalent circuit model and uses circuit simulation techniques to solve for an optimal solution, is applied to the state estimation problem for power systems. The benefits of using an equivalent circuit formulation for incorporating both Phasor Measurement Units (PMU) and Remote Terminal Units (RTU), as well as for reducing the nonlinearities of the state estimation problem was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Poor computational speed of the NECF-SE estimator is mainly a consequence of the use of commerical nonlinear solver. However, it can be significantly improved by utilizing a circuit approach to solve the NECF-SE's optimization problem instead [22].…”
Section: Numerical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Poor computational speed of the NECF-SE estimator is mainly a consequence of the use of commerical nonlinear solver. However, it can be significantly improved by utilizing a circuit approach to solve the NECF-SE's optimization problem instead [22].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…ECF has been leveraged recently to formulate a novel approach for SE in transmission systems, hence leading to the introduction of NECF-SE [20], [22] and LECF-SE [21] estimators. A brief overview of their similarities and differences will be presented below.…”
Section: B Ecf-based State Estimatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using this modeling approach and an optimization toolbox, a linear state estimation algorithm was introduced in [15]. Separately, it was demonstrated that it is possible to extend the ECF to natively solve optimization problems, including SE, within the same framework [16]- [18].…”
mentioning
confidence: 99%